2019
DOI: 10.1002/jcb.29244
|View full text |Cite
|
Sign up to set email alerts
|

miR‐153‐3p regulates progression of ovarian carcinoma in vitro and in vivo by targeting MCL1 gene

Abstract: The study of either miR‐153‐3p or MCL1 gene in ovarian carcinoma (OVC) has been reported; however, the interaction between miR‐153‐3p and MCL1 gene in OVC as well as the influence of their interaction on OVC progression has not been reported yet. Herein we intended to study the effects of miR‐153‐3p/MCL1 axis in OVC. Web‐based bioinformatics algorithms including DIANA TarBase 8.0, PicTar, and TargetScan Human 7.2 were used to predict the microRNAs (miRNAs) that could target MCL1 mRNA. Patient characteristics d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…1B ). Previous studies have indicated that miR-153 functions as a tumor suppressor in several malignancies, such as non-small cell lung cancer (NSCLC) ( 21 ) and ovarian carcinoma (OC) ( 14 ). Therefore, miR-153 was selected for further analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B ). Previous studies have indicated that miR-153 functions as a tumor suppressor in several malignancies, such as non-small cell lung cancer (NSCLC) ( 21 ) and ovarian carcinoma (OC) ( 14 ). Therefore, miR-153 was selected for further analyses.…”
Section: Resultsmentioning
confidence: 99%
“…For example, miR-153 has been shown to target the inhibitor of growth protein 2 to inhibit acute lymphoblastic leukemia cell proliferation, migration and invasion ( 13 ). It has also been reported that miR-153 can inhibit the MCL1 gene, thus suppressing the progression of ovarian carcinoma in vitro and in vivo ( 14 ). In addition, miR-153 has been reported to inhibit the migration and the tube formation of endothelial cells by blocking the paracrine of angiopoietin 1 in breast cancer cells ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs modulate their target genes in a sequencespecific manner and their roles in cancers have been largely investigated. [27][28][29] Of note, SERBP1 was ascertained as a target of miR-320a. Importantly, TMPO-AS1 silencing and overexpression of miR-320a conspicuously lessened the mRNA level and protein expression of SERBP1 in HCC cell.…”
Section: Discussionmentioning
confidence: 99%
“…Mir-153-3p is a miRNA that plays a key role in disease progression. It has been reported that miR-153-3p plays an anticancer role in human cancers including melanoma [18] , gastric cancer [12] and ovarian cancer [3] . Through bioinformatics analysis, we found that KLF5 is the potential target gene of miR-153-3p.…”
Section: Introductionmentioning
confidence: 99%